Exploring Research Trends of ChatGPT in Education Through Bibliometric Analysis - Nugroho, Listyanto Aji (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
This study delves into the burgeoning field of ChatGPT's integration into educational contexts through comprehensive bibliometric analysis. By examining publication patterns, research themes, influential works, and productive institutions, insights are cultivated into the current state of research in this domain. Notably, the analysis reveals a growing interest in ChatGPT for education, evidenced by the increasing volume of research efforts dedicated to this topic. Key research themes, such as the impact of ChatGPT on teaching and learning experiences, emerge prominently, highlighting the diverse applications and potential implications of this technology in educational settings. Moreover, the identification of influential works and productive institutions underscores the collaborative nature of research in this field and provides valuable references for researchers and practitioners. However, the study also acknowledges limitations, including the reliance on specific databases and the emphasis on quantitative metrics. Future research endeavors are recommended to address these limitations and explore distinct subcategories within ChatGPT for education to further deepen understanding and inform practical strategies for leveraging this technology to enhance educational practices.